A novel case of Greenberg dysplasia and genotype-phenotype correlation analysis for LBR pathogenic variants: An instructive example of one gene-multiple phenotypes. - Giorgio, Elisa; Sirchia, Fabio; Bosco, Martino; Sobreira, Nara Lygia M; Grosso, Enrico; Brussino, Alessandro; Brusco, Alfredo (Am J Med Genet A, 2019)
Greenberg skeletal dysplasia is an autosomal recessive, perinatal lethal disorder associated with biallelic variants affecting the lamin B receptor (LBR) gene. LBR is also associated with the autosomal recessive anadysplasia-like spondylometaphyseal dysplasia, and the autosomal dominant Pelger-Huët anomaly, a benign laminopathy characterized by anomalies in the nuclear shape of blood granulocytes. The LBR is an inner nuclear membrane protein that binds lamin B proteins (LMNB1 and LMNB2), interacts with chromatin, and exerts a sterol reductase activity. Here, we report on a novel LBR missense variant [c.1379A>G; p.(D460R)], identified by whole exome sequencing and causing Greenberg dysplasia in two fetuses from a consanguineous Moroccan family. We revised published LBR variants to propose a genotype-phenotype correlation in LBR associated diseases. The diverse phenotypes are correlated to the functional domain affected, the heterozygous or homozygous state of the variants, and their different impact on the residual protein function. LBR represents an instructive example of one gene presenting with two different patterns of inheritance and at least three different clinical phenotypes.